The Effectiveness of Oral Reading Practices on Students’ Pronunciation of Vocational High School - Nadilatul Jannah; Hanafi; Fitrotul Mufaridah (JELP Journal of English Language and Pedagogy, 2026)
Pronunciation is a major obstacle for many vocational high school students in learning English. Distinguishing mistakes are often caused by lack of practice, the habit of reading silently, and minimal direct correction from teachers. This hinders the development of students' speaking skills and reduces their confidence when communicating. This study aims to determine the effect of oral reading techniques on the pronunciation skills of vocational high school students. This technique was chosen because it can train the pronunciation of phonemes, articulation, intonation and rhythm directly through oral reading activities. This study used a quantitative approach with a true experiment design, with a pre-test and post-test control group involving 50 grade XI students who were divided into two groups, namely the experimental group (implementing oral reading) and the control group (using silent reading). The experimental group received treatment in the form of oral reading activities guided directly by the teacher, including reading text exercises with a focus on phoneme pronunciation, articulation, and correct intonation and rhythm. Students received direct correction and repeated practice, so that pronunciation errors could be gradually corrected. The post-test results showed that this technique was effective, with an average score increase of 28.2 points, compared to the control group which only increased by 11.1 points after regular learning (silent reading). This proves that oral reading improves students' pronunciation performance more effectively. The statistical test results show that the oral reading technique is proven effective in improving the English pronunciation of vocational high school students.